Caracterización de residuos sólidos urbanos en las unidades educativas de la ciudad de Macas, mediante la aplicación de normas mexicanas (nmx – aa - 015-019-022-061 – 1985), para proponer un plan de manejo ambiental - Velín Fárez, David Fernando (2015)
The rapid population growth has its consequences as the generation of waste, which is a social and environmental problem. We are going to treat this problem on a particular population, on the Educational Units of Macas city, Ecuador, where the inadequate management of the waste makes a landscape visual contamination. Morever, it causes contamination of air, water and soil. So, we pretend with this sustainable project, the Environmental Management Plan of the Municipal Solid Waste (MSW), to care the environment of this city and, to generate income using this solid waste. The methodology of this project was conducted in 3 stages, in every educational institution. The first stage consisted on the training to the students about how to manage the MSW. The second stage was about the characterization of MSW based on the use of Mexican standards. And, in the third stage, we developed the Management Plan of Solid Waste. Concluding, we could determinate that the “Don Bosco” educational institution generates 438.90 kg of solid waste per week. While, the “María Auxiliadora” and the Emanuel educational institution generates 209.69 kg, and 195.98 kg, respectively. Finally, the “Purísima de Macas” generates 119.11 kg of solid waste